MicroRNA-153 functions as a tumor suppressor in gastric cancer via targeting Kruppel-like factor 5 - Ouyang, Yanlan (Exp Ther Med, 2018)
Various microRNAs (miRs) have been demonstrated to serve important roles in gastric cancer (GC). miR-153 in particular has been reported to serve a suppressive role in GC; however, the underlying mechanism remains unclear. In the present study Reverse transcription-quantitative polymerase chain reaction and western blot analysis were used to examine the mRNA and protein expression of Kruppel-like factor 5. An MTT, wound healing and transwell assay were used to study cell proliferation, migration and invasion, respectively. In the present study, quantitative polymerase chain reaction data indicated that miR-153 was significantly downregulated in GC tissues compared with the adjacent non-tumor tissues. In addition, the reduced expression of miR-153 was significantly associated with GC aggressiveness and poor prognosis of patients. The expression of miR-153 was also reduced in GC cell lines, including KATO III, NCI-N87, SNU-16 and SNU-5, when compared with normal gastric epithelial GES-1 cells. Overexpression of miR-153 in the GC SNU-5 cells by miR-153 mimic transfection significantly inhibited the cell proliferation, migration and invasion. Furthermore, KLF5 was identified as a target gene of miR-153 in SNU-5 cells by bioinformatics prediction. It was observed that KLF5 was significantly upregulated in GC tissues and cell lines, and its expression was negatively regulated by miR-153 in SNU-5 cells. Overexpression of KLF5 impaired the suppressive effects of miR-153 on the proliferation, migration and invasion of SNU-5 cells. In conclusion, the present study demonstrated that miR-153 serves a tumor suppressive role in GC, at least partly, through directly targeting KLF5, thus highlighting the clinical significance of miR-153 in GC.